Climate-smart agricultural practices for improved livelihoods of small-scale farmers in Ethiopia - Hagos, Fitsum; Haileslassie, Amare (International Water Management Institute, 2024)
While Ethiopia contributes only 0.53% to global greenhouse gas emissions, the effect of climate change on the livelihoods of Ethiopian smallholder farmers, who have weak adaptive capacity, is adverse. Ethiopia’s climate projections show continued warming and unpredictable changes in rainfall patterns. The country is characterized by the frequency of droughts and other extreme events affecting agriculture, health and water. Projections indicate that climate change will reduce the productivity of the agriculture sector in the coming decades. Agriculture is recognized as a highly vulnerable sector to climate change, and the risks from climatic variations pose an imminent danger to food security and sustainability of livelihoods globally, requiring climate-smart adaptation interventions.